Kinetic and thermodynamic studies of adsorption of heavy metal ions from fuel ethanol. (25th September 2012) - Wang, Zengdi; Yin, Ping; Qu, Rongjun; Yin, Gui
The cleaning treatment of fuel ethanol plays an important role in its effective utilisation, and adsorption is one useful process to remove heavy metal ions from fuel ethanol solutions. In this work, a novel silica gel adsorbent functionalised with an aminophosphonic acid (denoted as SG-T-P) was developed, characterised, and used to remove heavy metal ions from fuel ethanol solutions. The adsorption properties of SG-T-P for Hg(II), Cu(II), Mn(II), Co(II), Zn(II), Ni(II), Fe(III) and Cd(II) in ethanol solutions were studied, revealing that SG-T-P had an excellent adsorption capacity for Hg(II). Furthermore, the kinetic data indicated that the adsorption process was governed by film diffusion and followed a pseudo-second-order rate model for SG-T-P. The thermodynamic parameters ΔG, ΔH and ΔS were 6.80 kJ mol–1 (35°C), 55.49 kJ mol–1, and 203.92 J K–1 mol–1, respectively. Thus, SG-T-P is effective and useful for the removal of Hg(II) from fuel ethanol solutions, and its good adsorption ability make it a promising candidate material for mercury uptake.